New combinations and names in Heliotropium (Heliotropiaceae) from South America, including a new occurrence for the flora of Ecuador - Miranda De Melo, José Iranildo (Phytotaxa, 2022)
Nine new combinations including two new names in South American species of Heliotropium (Heliotropiaceae) are proposed in this work: H. antioquianum J.I.M.Melo, replacement name; H. brevilobatum (K.Krause) J.I.M.Melo, comb. nov.; H. fuliginosum (Kunth) J.I.M.Melo, comb. nov.; H. gigantifolium (Killip ex J.S.Mill.) J.I.M.Melo, comb. nov.; H. macrostachyum (Rusby) J.I.M.Melo, comb. nov.; H. rollotii (Killip) J.I.M.Melo, comb. nov.; H. romeroi (I.M.Johnst.) J.I.M.Melo, comb. nov.; H. scabridum (Kunth) J.I.M.Melo, comb. nov., and H. stapfianum J.I.M.Melo, replacement name. Furthermore, Heliotropium romeroi is recorded for the first time in Ecuador and lectotypes are provided for Tournefortia brevilobata K.Krause, T. fuliginosa Kunth, T. macrostachya Rusby, and T. scabrida Kunth.